MACROPHAGE AGREGATES IN BROOK BARBEL BARBUS CF. PELOPONNESIUS SPLEEN AS INDICATORS OF ENVIRONMENTAL POLUTION - Maja Jordanova, Marija Naskovska, Vasil Kostov, Katerina Rebok (Section of Natural, Mathematical and Biotechnical Sciences, MASA, 2016)
Changes in fish macrophage aggregate centres (MACs) are a useful indicator of environmental stress. In this study we evaluated stereologically the values of these cells in the polluted sites compared to the clean site in the River Bregalnica. MACs aggregates were randomly distributed in spleen and often showed irregular form. Dominant pig- ment in them was hemosiderin. Relative volume of MACs aggregates showed significant higher value in brook barbel from polluted site. Total volume showed the same pattern, but differences were not significant. Our data confirm that increase in MACs aggregates may serve as to warn on potential pollution in aquatic ecosystems. However, the pre- caution is strongly suggested, as results were based on quantitative approach.
Keywords: spleen; macrophage aggregates centres; pollution